Comparison Of Audio Signal Compression Techniques - Lim, Suleen (2003)
This project investigates the signal compression potential and signal-to-noise ratios for audio signal based on four different source-coding techniques. They are the Fast Fourier Transform with Huffman Coding, Discrete Wavelet Transform with Huffman Coding, Differential Pulse Code Modulation, and Delta Modulation.